Rethinking French Translation Pedagogy in the Digital Age: Towards an Integrated Conceptual Framework (DIGITRANS) for Nigerian Universities - Shuaibu, Gloria N. (NIU Journal of Humanities; Vol 11 No 1 (2026): NIU Journal of Humanities, Vol. 11 No. 1, March 2026DO - 10.58709/niujhu.v11i1.2468, 2026)
The digital transformation of higher education has profoundly reshaped pedagogical practices, particularly in the field of translation training where digital technologies now function both as professional tools and as collaborative learning environments. This article critically examines the current state of French translation pedagogy in Nigerian universities and proposes an integrated conceptual framework, the DIGITRANS model, designed to address persistent pedagogical and technological gaps. Drawing on social constructivism and theoretical frameworks of educational digital competence, the study develops a model structured around five interrelated dimensions: translational competence, digital competence, guided autonomy, collaboration, and cultural reflexivity. Through a conceptual analysis of the literature on translation pedagogy and educational technologies, the article highlights the need to move from a transmissive teaching model toward a more interactive, collaborative, and learner-centered approach. The proposed model demonstrates how the integration of Computer-Assisted Translation (CAT) tools, collaborative platforms, and authentic translation projects can enhance students’ professional readiness. In the Nigerian context, the DIGITRANS framework offers both a theoretical and pedagogical response to challenges related to limited digital infrastructure, low technological literacy, and curriculum misalignment. The article concludes that adopting this model could contribute to modernizing translation training in African universities by aligning it with international standards while promoting inclusive, critical, and technologically integrated pedagogy. Keywords: Translation pedagogy; Digital competence; Computer-assisted translation (CAT); Social constructivism; Nigerian universities